2009
DOI: 10.1309/ajcp18onzutdugaq
|View full text |Cite
|
Sign up to set email alerts
|

Chromogenic Media vs Real-Time PCR for Nasal Surveillance of Methicillin-ResistantStaphylococcus aureus

Abstract: Surveillance for methicillin-resistant Staphylococcus aureus (MRSA) colonization can be an important element for infection control programs when managing a multidrug-resistant pathogen such as MRSA. The sensitivity and speed of laboratory testing affects the proportion of appropriate isolation days captured, which determines the success or failure of a MRSA control program. Chromogenic culture, CHROMagar MRSA (BBL, Becton Dickinson, Sparks, MD) and MRSASelect (Bio-Rad, Hercules, CA), with and without broth enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 26 publications
4
30
0
1
Order By: Relevance
“…Similar performance of a chromogenic medium and RT-PCR has also been reported in another study (Bischof et al, 2009). However, yet another study has reported that molecular techniques give quick results with high sensitivity (Paule et al, 2009). Brilliance TM MRSA agar (Oxoid) is also a good, cost effective medium for the detection of MRSA because cost of screening on conventional culture medium is similar to the cost of chromogenic medium.…”
Section: Discussionsupporting
confidence: 61%
“…Similar performance of a chromogenic medium and RT-PCR has also been reported in another study (Bischof et al, 2009). However, yet another study has reported that molecular techniques give quick results with high sensitivity (Paule et al, 2009). Brilliance TM MRSA agar (Oxoid) is also a good, cost effective medium for the detection of MRSA because cost of screening on conventional culture medium is similar to the cost of chromogenic medium.…”
Section: Discussionsupporting
confidence: 61%
“…Key to the decision process is selection of a testing system with sufficient sensitivity and result reporting time so that a combination of these factors will enable placing patients in contact precautions for 80% of the time they are in the hospital (9,25,26). This is critical since the most expensive AST program is one where testing is done, but MRSA clinical disease is not reduced, an outcome to be avoided.…”
Section: Resultsmentioning
confidence: 99%
“…Although they are less costly, direct chromogenic agar cultures are insensitive compared to PCR (15,22). Broth enrichment in tryptic soy broth (TSB) prior to plating has been shown to increase the sensitivity of chromogenic techniques but also increases the workload and the time to result, making this method problematic for routine use in the clinical microbiology laboratory (11).…”
mentioning
confidence: 99%